The focus of Langenbeck’s Archives of Surgery in the 21st century - Schneider, Martin; Weitz, Jürgen; Büchler, Markus W. (Langenbeck's archives of surgery, 2010)
The Langenbeck's Archives of Surgery has been serving as a publication platform for clinical and scientific progress in the field of surgery for 150 years. In order to maintain this long-standing tradition throughout the coming decades, it will be mandatory to face the challenges posed by increasing specialization of surgical subdisciplines, modern technologies, and interdisciplinary treatment options.